Models of Institutional Organization of Budgetary Control in Foreign Countries - SARKISYAN, Zhaklin M. (Journal of Advanced Research in Law and Economics; Vol 9 No 1 (2018): JARLE Volume IX Issue 1(31) Spring 2018DO - 10.14505//jarle.v9.1(31).34, 2018)
The article discusses some of the features, showing that experts distinguish the following models of institutional organization of budgetary control: parliamentary control, administrative control, judicial control. Parliamentary control in the field of Finance to produce to the Commission or parliamentary committees or audit bodies, for example, the chamber. Exercising budgetary control committees have certain features in different States as the order of the information and competence. Administrative and financial control in the public sectors the head of state, government and specialized bodies, in addition, ministries and agencies. Judicial financial control in the public sector carry out so-called judicial or quasi-judicial bodies, for example, the court of accounts in France, Italy, Spain etc.